Some common fixed point theorems in fuzzy metric spaces using compatible of type A-1 and A-2 - Aage, CT; Salunke, JN (Kathmandu University Journal of Science Engineering and Technology, 2011)
Recently M. S Khan, H. K. Pathak and R. George [9] have been introduced the concept of compatible of type A − 1 and type A − 2 and obtained some common fixed point theorems in fuzzy metric spaces. In this connection we have proved some common fixed point theorems in fuzzy metric space using semicompatible mappings.